Conflict in the Shadow of Conflict - Se Hoon Bang; Jae Soo Kim (KDI Journal of Economic Policy, 2016)
We study how an advantage given to an interim winner in sequential conflicts characterizes dynamic competition between players and influences their payoffs. As the intensity of competition during each period is negatively correlated, perfect security is not necessarily desirable for contending parties. We present results which are widely applicable to various types of dynamic competition, where competition in each period is linked to the interim winner's relative advantage. Policy implications are also discussed in a variety of areas, and several extensions are explored.
Keywords: D44; D74; O31; 330; Sequential Conflicts; AllPay Auctions; Sequential Innovations; Arms Race